Social Responsibility in Tourism: How Indonesia’s Tourism Industry Can Address Economic Disparities (Indonesian Tourism Justice Review, 2025)
The rapid growth of Indonesia’s tourism industry has contributed significantly to the nation’s economy, but it has also exacerbated economic disparities, particularly between urban and rural areas. This paper examines how social responsibility initiatives within the tourism sector can address these growing inequities. Focusing on regions such as Bali and Yogyakarta, the study analyzes how the tourism industry can better align with social justice principles to ensure that local communities benefit equitably from tourism revenue. The research examines the role of corporate social responsibility (CSR) programs, fair trade tourism, and community-based initiatives in redistributing economic benefits. Drawing on case studies from local businesses and international tourism operators, the paper identifies best practices and challenges in promoting inclusive economic growth. The study advocates for policy reforms that incentivize responsible tourism practices, ensure fair wages for workers, and promote local entrepreneurship. The paper concludes by proposing a model of inclusive tourism that fosters economic justice and reduces the widening wealth gap in Indonesia’s tourist destinations.